Involvement of Xeroderma Pigmentosum Group A (XPA) in Progeria Arising from Defective Maturation of Prelamin A - Liu, Yiyong (2007)
Cellular accumulation of DNA damage has been widely implicated in cellular senescence, aging, and premature aging. In Hutchinson-Gilford progeria syndrome (HGPS) and restrictive dermopathy (RD), premature aging is linked to accumulation of DNA double-strand breaks (DSBs) which results in genome instability. However, how DSBs accumulate in cells despite the presence of intact DNA repair proteins remains unknown. Here we report that the recruitment of DSB repair factors Rad50 and Rad51 to the DSB sites, as marked by γ-H2AX, was impaired in human HGPS and Zmpste24-deficient cells. Consistently, the progeria-associated DSBs appeared to be unrepairable although DSBs induced by camptothecin were efficiently removed in the progeroid cells. We also found that these progeroid cells exhibited nuclear foci of XPA, a unique nucleotide excision repair protein. Strikingly, these XPA foci colocalized with the DSB sites in the progeroid cells. This XPA-DSB association was further confirmed, and found to be mediated by DNA, using a modified chromatin immunoprecipitation assay and co-immunoprecipitation. RNAi knockdown of XPA in HGPS cells partially restored DSB repair as evidenced by Western blot analysis, immunofluorescence and comet assays. We propose that the uncharacteristic localization of XPA to or near DSBs inhibits DSB repair, thereby contributing to the premature aging phenotypes observed in progeria arising from genetic defects in prelamin A maturation.